(3eONd eYGUQ aj GdeMGSHI GdEOGQjI GdeJbOeIs - (3CMeO QLH(B, (3YHO GdYGds; (3aJMj QRb GdShGajQj(B, s ((3GdGScfOQjI(B:s (3OGQ GdLGeYI GdLOjOI(B,s, 2002)
(3CgejI fXGe GdeYdheGJ GdeMGSHj, WHjYI YedjI GJNGP GdbQGQGJ GdGOGQjI, GdJMdjd GdJaGVdj hGdbQGQGJ GdGOGQjI, GdefXhQ GdGSJQGJjLj ddeMGSHI GdGOGQjI, OhQ GdeYdheGJ GdeMGSHjI aj GJNGP bQGQGJ GdJSYjQ, bQGQGJ GdLhOI, JMdjd GdYdGbI Hjf GdJcdaI hGdMLe hGdQHM, GdJMdjd GdeGdj ddCZQGV GdGOGQjI, eDTQGJ bjGS GdGfJGLjI, CKQ GNJdGa eOGNd JNUjU GdJcGdja ZjQ GdeHGTQI Ydi GdbQGQGJ GdGOGQjI, OhQ GdeMGSHI GdGOGQjI aj JMdjd YfUQ GdeNRhf, HQeLI GdCgOGa hJNWjW GdCfTWIs
Keywords: (3GdEOGQIs; (3GdeMGSHIs